The role of self regulated learning in the covid-19 pandemic era - Fida Hudaifah (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2020)
Beginning in 2020, the world situation is very alarming with the co-19 pandemic, in the covid-19 pandemic era the order to remain in the house simultaneously would bring more free time for students. Students should be able to take advantage of existing situations with conducive learning activities at home, for this purpose students must have their own strategies that support students. The purpose of writing this article is 1. Analyzing the role of self-regulated learning in the co-pandemic era of 19, 2. To describe the self-regulated learning strategy in the co-pandemic era. Method: reference research type of research, object of self regulared learning research, data validity is done by tringulation of sources and extension of time, data analysis techniques using constant comparison. There are two research results namely 1. Self-regulated learning affects the ability of problem solving, learning outcomes, mathematical connection abilities, self-regulated learning is related to academic procrastination in accelerated learners, and is related to learning achievement. 2. Self-regulated learning strategies during the co-19 pandemic, namely the preparation phase, the implementation stage, and the reflection stage.